Application of Capillary and Free-Flow Zone Electrophoresis for Analysis and Purification of Antimicrobial β-Alanyl-Tyrosine from Hemolymph of Fleshfly Neobellieria bullata - Šolínová, Veronika; Sázelová, Petra; Mášová, Alice; Jiráček, Jiří; Kašička, Václav (Molecules, 2021)
The problem of a growing resistance of bacteria and other microorganisms to conventional antibiotics gave rise to a search for new potent antimicrobial agents. Insect antimicrobial peptides (AMPs) seem to be promising novel potential anti-infective therapeutics. The dipeptide β-alanyl-tyrosine (β-Ala-Tyr) is one of the endogenous insect toxins exhibiting antibacterial activity against both Gram-negative and Gram-positive bacteria. Prior to testing its other antimicrobial activities, it has to be prepared in a pure form. In this study, we have developed a capillary zone electrophoresis (CZE) method for analysis of β-Ala-Tyr isolated from the extract of the hemolymph of larvae of the fleshfly Neobellieria bullata by reversed-phase high-performance liquid chromatography (RP-HPLC). Based on our previously described correlation between CZE and free-flow zone electrophoresis (FFZE), analytical CZE separation of β-Ala-Tyr and its admixtures have been converted into preparative purification of β-Ala-Tyr by FFZE with preparative capacity of 45.5 mg per hour. The high purity degree of the β-Ala-Tyr obtained by FFZE fractionation was confirmed by its subsequent CZE analysis.
Keywords: larva; Dipeptides; Animals; antiinfekční látky; Chromatography, High Pressure Liquid; Electrophoresis; Hemolymph; dipeptidy; hemolymfa; Sarcophagidae; elektroforéza; Larva; vysokoúčinná kapalinová chromatografie; zvířata; Anti-Infective Agents